Factores de riesgo y las principales causas de la rinofaringitis en niños menores de 10 años en la Unidad de Educación Básica 24 de Mayo, Baba octubre 2018 – abril 2019 - Gurumendi Junco, Ricardo Stalyn (2019)
Respiratory infection is a public health problem, frequent in children under 10 years of age in the outpatient clinic of family or pediatric medicine. The most common respiratory infection, Rhinopharyngitis, regardless of whether it was due to a viral agent (the most common being a rhinovirus). According to the definition of the clinical practice guide, they would only be viral processes. In addition, if these minors, had or not fever, during the course of the respiratory picture. Some of the factors that condition their presentation are nutritional status, home care, breastfeeding. The main objective of this research was to establish the factors of rhinopharyngitis in children under 10 years of age in the Basic Education Unit "24 de Mayo", after a field analysis and conducting the surveys it was concluded that it is important the implementation of a awareness campaign that allows parents to have knowledge about the prevention, hygiene and care measures of a person (child) who is going through a flu, cold or rhinopharyngitis, as well as interacting with others children of your school, how your behavior should be and the importance of avoiding self-medication.